Effectiveness of Kenya’s Community Health Strategy in Delivering Community-based Maternal and Newborn Health Care in Busia County, Kenya: - Wangalwa, Gilbert; Cudjoe, Bennett; Wamalwa, David; Machira, Yvonne; Ofware, Peter; Ndirangu, Meshack; Ilako, Festus (Pan African Medical Journal)
Background: Maternal mortality ratio and neonatal mortality rate trends in Kenya have remained unacceptably high in a decade. In 2007, the Ministry of Public Health and Sanitation adopted a community health strategy to reverse the poor health outcomes in order to meet Millennium Development Goals 4 and 5. It aims at strengthening community participation and its ability to take action towards health. The study aimed at evaluating the effectiveness of the strategy in improving maternal and neonatal health outcomes in Kenya. Methods: Between 2008 and 2010, the African Medical and Research Foundation implemented a community-based maternal and newborn care intervention package in Busia County using the community health strategy approach. An interventional, non-randomized pre-test post test study design was used to evaluate change in essential maternal and neonatal care practices among mothers with children aged 0 - 23 months. Results: There was statistically significant (p<0.05) increase in attendance of at least four antenatal care visits (39% to 62%), deliveries by skilled birth attendants (31% to 57%), receiving intermittent preventive treatment (23% to 57%), testing for HIV during pregnancy (73% to 90%) and exclusive breastfeeding (20% to 52%). Conclusion: The significant increase in essential maternal and neonatal care practices demonstrates that, community health strategy is an appropriate platform to deliver community based interventions. The findings will be used by actors in the child survival community to improve current approaches, policies and practice in maternal and neonatal care.
non-randomized pre-test post test study
This article is published as part of the supplement “AMREF´s evidence in advancing the health of women and children” Supplement sponsored by AMREF - African Medical and Research Foundation © Gilbert Wangalwa et al. The Pan African Medical Journal - ISSN 1937-8688. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.
Keywords: Neonatal care; Maternal care; Community-based care; Community health strategy; AMREF; Community health worker; Busia; Child survival